Journey of digital transformation: a case study of the State Bank of India. (11th April 2022) - Suvarna, Harinakshi; Kayarkatte, Narayan
Digital banking is the major step towards online banking, in which banking services are provided over the internet. The resultant advantages for banks and customers are faster and more convenient banking services. Through digitisation, SBI has transformed its physical operations into virtual operations. In the competitive environment that drives the technology generation today, banks are making use of technology to make it attractive to their customers. Banks in the new age have more privileges with all digital infrastructures and services than traditional banks that were active at the time. Bank of Calcutta was the first bank to be established in India in 1806 and later turned into the SBI. As the Indian subcontinent's oldest commercial bank, SBI boosts the country's trillion-dollar economy and meets the aspirations of its large population. This study focuses on SBI's path from the traditional banking process to the modern digital banking process. This study may help to understand SBI's detailed digital journey from the beginning. The survey data analysis also underlines the advantages and disadvantages of virtual banking.